ASESMEN PEMBELAJARAN BIPA TINGKAT 3 BERWAWASAN GORONTALO MENGGUNAKAN APLIKASI WORDWALL - Prasetia, Udin; Kadir, Herson (Universitas Negeri Gorontalo, 2024)
The BIPA learning assessment is an integral part of learning, so planning and designing assessments that are appropriate to the learning components are needed. The focus of this research problem is (1) How to plan a level 3 BIPA learning assessment with a Gorontalo insight, (2) How to design a level 3 BIPA learning assessment with a Gorontalo insight using the Wordwall application. The aims of this study were: (1) to describe the BIPA level 3 learning assessment plan with the Gorontalo insight, (2) to describe the design of the BIPA level 3 learning assessment with the Gorontalo insight using the Wordwall application. This research includes qualitative research, the research method is descriptive qualitative. This research is based on the BIPA learning evaluation theory by Ari Kusmiatun. The results of this study are BIPA level 3 learning assessment planning based on graduate competency standards, the form of the assessment instrument is a language test (vocabulary and grammar) totaling 12 test questions, with the theme of Gorontalo insight. The design of a level 3 BIPA learning assessment uses a wordwall application which consists of 3 parts, namely gap entries, random sentences, and interactive quizzes.